Travelling Savage Spaces: Jean de Léry and the “Antarctic France”, Brazil 1555–60 - Eriksson, Jonnie (2008)
The paper compares Jean de Léry's account of his experiences of the French colonization of the coast of Brazil in the mid 16th century with the account made by his contemporary André Thevet. Instead of focussing on how the native tribes were depicted in icolonial discourse or how they were treated in reality, this analysis brings to the fore how the description of space from the point of view of the travelling subject can be shown to provide a "cartography" or "topography" of the process of colonization, in which the properties of identity begin to deterritorialize. From a perspective of the theory of Deleuze and Guattari, the becoming-colonial is thus tied to a becoming-savage.